THE ANALYSIS OF COMMUNICATIVE TRANSLATION AT THE OPENING SPEECH OF THE KTT G-20 BALI SUMMIT BY THE PRESIDENT JOKOWI: “WE MUST END THE WAR” - Juliana; Tia Fahira Putri Army (Pusat Riset dan Inovasi Nasional, 2021)
This research entitles the analysis of communicative translation at the opening speech of the KTT G-20 Bali Summit by President Jokowi: We must end the war”. The use of communicative language in translating text using the communicative translation method. Communicative language is used so that readers or listeners can take meaning from the contents of the text in accordance with the meaning that has been written by the author. This communicative language is always successful if it is used in the same language as the target language. However, it will be very much different. If the contents of the text use a different language. Then the translator must be able to translate the contents into the text in the target language. This is a little difficult to implement because translators still find it difficult to distinguish between free translation and communicative translation. Therefore, the translator must first analyze the text whether it is in accordance with the linguistic aspects or its content so that it can be accepted and understood by the reader. In this case, this research is based on the translation carried out in the speech of Opening Speech KTT G20 Bali Summit by President Jokowi: We Must End the War. This research used a descriptive qualitative method. This research was conducted to describe and find out what form of communicative language that used in speech text. It also aims to compare the meaning of the original speech text with the translated text, whether the meaning of the two texts remains the same or changes. In addition, it is a source for readers to know how to analyze communicative translation.